Sex differences in fingerprint ridge density in a Turkish young adult population: A sample of Baskent University. (May 2015) - Oktem, Hale; Kurkcuoglu, Ayla; Pelin, Ismail Can; Yazici, Ayse Canan; Aktaş, Gulnihal; Altunay, Fikret
Abstract: Fingerprints are considered to be one of the most reliable methods of identification. Identification of an individual plays a vital part of any medico-legal investigations. Dermatoglyphics is a branch of science that studies epidermal ridges and ridge patterns. Epidermal ridges are polygenic characteristics that form intrauterine 10–18 weeks and considered fully developed by the sixth month of fetal growth. Fingerprints are permanent morphological characteristics and criminal detection based on fingerprints is based on the principle that no two people can have identical fingerprints. Sex determination from fingerprints has been examined in different population. In this study we aimed to study fingerprint ridge density in Turkish population sample of Baskent University students. Fingerprints were obtained from 118 women, 88 men a total of 206 students aged between 17 and 28 years old by means of simple inking method. Fingerprints from all right and left hands fingers were collected in three different area of each. The ridges on fingerprints were counted diagonally on squares measuring 5 mm × 5 mm on radial, ulnar and inferior areas. The fingerprint ridge density in radial, ulnar and inferior areas and between sexes was compared statistically Mann Whitney U test and Friedman test. The ridge density was significantly greater in women in every region studied and in all fingers when compared to men. The fingerprint ridge density in the ulnar and radial areas of the fingerprints was significantly greater than the lower area. Fingerprint ridge density can be used by medico-legal examination for sex identification. Highlights: We aimed to show the gender difference from the view point of fingerprint ridge density. Fingerprint ridges were counted in 5 mm 2 areas on radial, ulnar and inferior regions of each finger. The ridge density was significantly greater in women in every region in all fingers. The most significant difference between the genders was seen in the radial region while the least was in the inferior region. The results of the study indicate that fingerprint ridge density can be used for sex determination.